Development of an Integrated Science Literacy Assessment Instrument Incorporating Local Gamelan Wisdom in the Topic of Sound Waves to Support the Achievement of SDG 4: Quality Education - Ayunda Zahra Aulia; Titin Sunarti; Joshi Maharani Wibowo (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to develop an essay-based science literacy assessment instrument that integrates local gamelan wisdom into the topic of sound waves for high school students, in accordance with the PISA 2025 science literacy framework. Method: The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model was used, limited to the development stage. The instrument consists of ten essay questions, a question outline, and a scoring rubric. Validation was conducted by three experts, while the empirical test involved 35 students and was analyzed using the Rasch Model with Winsteps software. Results: Expert validation showed a validity score of 86% (highly valid). Rasch analysis indicated that all test items met the criteria for empirical validity, with Point-Measure Correlation values ranging from 0.36 to 0.77 and MNSQ values ranging from 0.52 to 1.35. The item reliability coefficient of 0.91 falls into the “very good” category, while the person reliability coefficient of 0.76 falls into the “adequate” category. The Wright Map shows item difficulty levels ranging from −1.20 to +4.00 logits, supported by an item separation index of 2.91, indicating the instrument’s strong ability to distinguish difficulty levels. Novelty: The novelty of this study lies in the integration of the acoustic phenomena of the local wisdom of gamelan into a science literacy instrument in the form of an essay, which is aligned with the PISA 2025 framework and tested using the Rasch Model. This instrument has proven to be suitable for measuring students’ science literacy in a contextual manner while supporting cultural preservation and the achievement of SDG 4 of Quality Education.